The dust bowl - Duncan, Dayton (PBS America, 2012)
Draws on reports, newspaper articles, and interviews to chronicle the American Dust Bowl, providing photographs to illustrate the catastrophe as well as offer a tribute to man's relationship to the land and his ability to persevere
Orig.:USA, 2012
Special Features: Behind the scenes; deleted scenes; additional interviews
Keywords: Geschichte 1931-1939; Dokumentarfilm; Great Plains -- Süd; Dust Bowl Era, 1931-1939; Depressions / 1929 / Great Plains; Droughts / Great Plains / History / 20th century; Farmers / Great Plains / Social conditions / 20th century; Great Plains / History / 20th century; Great Plains / Social conditions / 20th century; Film; DVD-Video